2019
DOI: 10.1093/noajnl/vdz021
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recurrent glioblastoma after laser interstitial thermal therapy: The role of diffusion imaging

Abstract: Background Evaluate the utility of diffusion-weighted imaging (DWI) for the assessment of local recurrence of glioblastoma (GBM) on imaging performed 24 h following MRI-guided laser interstitial thermal therapy (LITT). We hypothesize that microscopic peritumoral infiltration correlates with early subtle variations on DWI images and apparent diffusion coefficient (ADC) maps. Methods Of 64 patients with GBM treated with LITT, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This would be disadvantageous as the ADC maps have also shown promising results with regard to identifying infiltrative patterns of glioma growth [32], predicting O 6 -methylguanine-DNA methyl-transferase (MGMT) methylation status [33] and predicting treatment outcomes and survival [33][34][35]. In addition, in patients who underwent laser interstitial thermal therapy for glioblastoma, the ADC value of the direct postoperative MRI scan (< 24 h) in the peritumoral region showed to be correlated with regions of later tumor recurrence [36].…”
Section: Discussionmentioning
confidence: 99%
“…This would be disadvantageous as the ADC maps have also shown promising results with regard to identifying infiltrative patterns of glioma growth [32], predicting O 6 -methylguanine-DNA methyl-transferase (MGMT) methylation status [33] and predicting treatment outcomes and survival [33][34][35]. In addition, in patients who underwent laser interstitial thermal therapy for glioblastoma, the ADC value of the direct postoperative MRI scan (< 24 h) in the peritumoral region showed to be correlated with regions of later tumor recurrence [36].…”
Section: Discussionmentioning
confidence: 99%
“…One active area of prognostication research is the use of imaging for prediction of GBM recurrence after LITT. Recent analysis of postablation diffusion-weight imaging (DWI) sequences suggests that DWI may be able to predict specific locations for GBM recurrence [58]. The authors performed a retrospective review of 39 patients with GBM that had undergone LITT and postoperative MRI approximately 24 hours after ablation at a single institution.…”
Section: Developing Prognostication Tools In Litt For Gbmmentioning
confidence: 99%
“…Mohammadi et al suggested that areas of DWI signal decrease and an increase in apparent diffusion coefficient along the peritumoral areas in the 24 h post-LITT MRI could harbor residual tumor. These findings could potentially be used to identify areas of future progression and recurrence [29].…”
Section: Special Imaging Modalities In Littmentioning
confidence: 99%